Formation of rivers and mountains drives diversification of primitively segmented spiders in continental East Asia. (12th July 2018) - Xu, Xin; Kuntner, Matjaž; Liu, Fengxiang; Chen, Jian; Li, Daiqin
Abstract: Aim: Complex topography in continental East Asia mirrors geological events such as formation of rivers and mountains, but to what extent these events drive diversification remains underexplored. We address this question by testing vicariant hypotheses using the primitively segmented spider genera Sinothela and Ganthela, focusing on diversification within Sinothela . Location: Continental East Asia. Methods: We employ a three‐way test of six vicariant hypotheses derived from river and mountain formation: (a) phylogenetically, we evaluate the sister group relationships of lineages on either side of each barrier; (b) chronologically, we estimate the timing of splits in a time calibrated phylogenetic framework; (c) biogeographically, we infer whether each of these splits shows a reduction in ancestral areas. Results: Three‐way tests fully support five barrier formation events: (a) the Oligocene–Miocene origin of Sinothela + Ganthela coincides with the 23–36.5 Ma range of the Yangtze River formation; (b) the Sinothela split into lineages on each side of the Qinling–Dabie mountains overlaps with the estimated uplift (2.6–23 Ma); (c) the origin of lineages on each side of Taihang Mts fits its hypothesized uplift (3.6–5.3 Ma); (d) the origin of lineages on each side of mid‐lower Yellow River supports the timing of its formation (1.8–3.6 Ma); (e) lineages on each side of the Yellow River eastern Ordos bend coincide with its origin (1.6 Ma). However, the Taishan Mts uplift as barrier formation is only partially supported. Main conclusions: Our results suggest vicariant origins of Sinothela and provide evidence for continental‐wide vicariant events that have shaped these spiders' evolutionary history in continental East Asia. Our study also highlights how dated molecular phylogenies can narrow down too widely estimated time intervals of river and mountain formation by geologists. Primitively segmented spiders thus provide an excellent model for exploring how geological events shape biodiversity.